2001
DOI: 10.1007/s004020000216
|View full text |Cite
|
Sign up to set email alerts
|

Open wedge tibial osteotomy by hemicallotasis for medial compartiment osteoarthritis

Abstract: Early clinical results were evaluated for 22 adult patients who had undergone an open wedge tibial osteotomy by hemicallotasis (HCO) due to medial compartment osteoarthritis. The mean age at the time of the index operation was 56 (range 33-66) years. The mean duration of follow up was 16 (range 9-23) months. The median hip-knee-ankle angle (HKA) was 169 (range 162-186) deg preoperatively and 182 (range 175-191) deg at follow up. We did not observe any early collapse of the new bone wedge. The median time to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 10 publications
2
45
0
6
Order By: Relevance
“…Otherwise, if the osteotomy gap is too large, the correction can be performed gradually, beginning on the 7 th -10 th post-operative day, with emicallotaxis technique. The result is verified under image intensifier, a small amount of compression is performed, the rods are tightened and the skin is closed (Catagni et al, 1994;Klinger et al, 2001;Ohsawa et al, 2006;Viskontas et al, 2006).…”
Section: Treatmentmentioning
confidence: 90%
See 1 more Smart Citation
“…Otherwise, if the osteotomy gap is too large, the correction can be performed gradually, beginning on the 7 th -10 th post-operative day, with emicallotaxis technique. The result is verified under image intensifier, a small amount of compression is performed, the rods are tightened and the skin is closed (Catagni et al, 1994;Klinger et al, 2001;Ohsawa et al, 2006;Viskontas et al, 2006).…”
Section: Treatmentmentioning
confidence: 90%
“…Some Authors (Klinger et al, 2001;Ohsawa et al, 2006;Viskontas et al, 2006) suggested that an opening wedge HTO with emicallotaxis and external fixator is the treatment that should be chosen to correct the malalignment, however we prefer to use this technique with a circular external fixator (Taylor Spatial Frame, Smith & Nephew, Memphis, Tennesseee) only in deformities that need a correction greater than 12.5°. In these cases HTO is associated to a greater rate of complications, such as delayed unions, nonunions and an unstable osteotomy, due to a too large osteotomy gap.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…Different types of the implants have been used for fixation of osteotomy. Less extensive implants would probably cause least disturbance for any future replacement procedures 9,11,12 . We used single staple for fixation as it is a simple procedure and the implant is cheap.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, tibial open-wedge osteotomy with hemicallotasis (HCO), a progressive distraction technique using an external fixator, has gained interest (Turi et al 1987, Fowler et al 1991, Magyar et al 1998, Klinger et al 2001, Weale et al 2001, Gerdhem et al 2002. HCO has several advantages over conventional high tibial osteotomy such as closed-wedge or dome osteotomy, including a smaller incision, easier acquisition of accurate correction, and allowance of earlier mobilization and weight bearing (Fowler et al 1991, Klinger et al 2001).…”
mentioning
confidence: 99%
“…HCO has several advantages over conventional high tibial osteotomy such as closed-wedge or dome osteotomy, including a smaller incision, easier acquisition of accurate correction, and allowance of earlier mobilization and weight bearing (Fowler et al 1991, Klinger et al 2001). In addition, we have shown that HCO lead to only little shortening of the patellar tendon and less distortion of the proximal tibia postoperatively, implying an easier subsequent conversion to TKA (Nakamura et al 2001).…”
mentioning
confidence: 99%